2015
DOI: 10.1111/jog.12745
|View full text |Cite
|
Sign up to set email alerts
|

Motor vehicle collision‐related accidents in pregnancy

Abstract: Pregnant women admitted to hospital after a collision-related MVA tend to sustain less severe injuries compared to non-pregnant women. However, the influence of admissions for fetal monitoring, rather than maternal injury, could not be determined from our dataset. Pregnant women who experienced a collision-related MVA also required less surgical intervention, with the exception of genitourinary surgery, which may be indicative of more cesarean deliveries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…The data were sourced from hospital records/trauma registries (7/19) 17 30 31 34 37 38 40 or from population-level databases (12/19). 2 6 8 26–29 32 33 35 36 39 The majority of studies collected information on outcomes of pregnant women involved in MVC during any trimester of pregnancy. Eight out of 19 studies reported information about the use of safety devices such as seat belts and/or airbags.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data were sourced from hospital records/trauma registries (7/19) 17 30 31 34 37 38 40 or from population-level databases (12/19). 2 6 8 26–29 32 33 35 36 39 The majority of studies collected information on outcomes of pregnant women involved in MVC during any trimester of pregnancy. Eight out of 19 studies reported information about the use of safety devices such as seat belts and/or airbags.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted our review using a prospectively registered protocol and reported it in accordance with the international standards. 41 This review, to our best knowledge, is the first one examining the link between involvement in MVC, mortality and adverse outcomes that involves evaluation of study quality assessment; 14 studies looking at outcome incidence related to MVC 2 17 29–40 and 5 studies comparing outcomes in pregnant women involved in MVC and those who were not. 6 8 26–28 We used established tools to assess outcome reporting quality for the incidence rates 42 and comparability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Pregnancy was defined as the presence of any of the following codes: 640–649, 650–659, 660–669, V22, V23, and V27. 10 Mechanical ventilation was isolated by the presence of the following International Classification of Diseases, 9th Revision codes: 96.70, 96.71, 96.72, and 96.04. Those patients with code 96.72 were defined as having prolonged mechanical ventilation (greater than 96 hours).…”
Section: Methodsmentioning
confidence: 99%